Karakteristik dan Persepsi Wisatawan Domestik Terhadap Restoran di Kawasan Denpasar Selatan - Agam, Dicky; Ariani, Ni Made; Sutaguna, I Nyoman Tri (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2023)
South Denpasar is one of the sub-districts in the city of Denpasar and is one of the areas used as a destination for domestic tourists. There are various types of restaurants so it is important to know how tourists perceive restaurants in the South Denpasar area. This study aims to determine the characteristics and perceptions of domestic tourists towards restaurants in the South Denpasar area. .The data sources of this research are primary (questionnaires, interviews, and observations) and secondary data (journals and previous research). The types of data used are qualitative and quantitative with the technique of determining the sample quota sampling by taking the sample accidental sampling of 60 respondents.Characteristics of domestic tourists based on origin, namely 88.3% originating from outside Bali, characteristics based on male gender 53.3%, characteristics based on age are in the age range 21-30 71.7%, based on latest education 60% SMA / SMK, based on marital status 93.3% single, based on work 61.7% students, based on total income 35.6% IDR 500,000 - IDR 2,000,000, based on travel destination 53.3% recreation and based on length of stay 41.7%> 7 days. The perception of domestic tourists towards restaurants in the South Denpasar area is that the perceived quality indicator gets the highest average score with a percentage of 4.14 (good), then the service quality indicator gets an average score of 4.1 (good), the food quality indicator gets an average score of 3.96 (good) and the price indicator got an average score of 3.92 (good). Based on the data that has been obtained, it can be seen that the perceptions of domestic tourist towards restaurants in the South Denpasar area fall into the good category with a percentage of 4.03 (good).